The development of an evaluation tool to assess professional behavior and clinical competencies from the graduates' perspective - Kusmiati M.; Bahari R.; Hamid N.A.A.; Emilia O.; Suhaila Sanip (Korean Society of Medical Education, 2024)
Indexed by Scopus